High Rate Performance for Carbon‐Coated Na3V2(PO4)2F3 in Na‐Ion Batteries. Issue 4 (16th September 2018) - Broux, Thibault; Fauth, François; Hall, Nikita; Chatillon, Yohann; Bianchini, Matteo; Bamine, Tahya; Leriche, Jean‐Bernard; Suard, Emmanuelle; Carlier, Dany; Reynier, Yvan; Simonin, Loïc; Masquelier, Christian; et al.
Abstract: The electrochemical and structural properties of a series of three different Na3 V2 (PO4 )2 F3 samples (with or without carbon coatings of different natures), obtained via different synthesis methods, are compared through operando high‐resolution synchrotron X‐ray diffraction. The pristine materials all possess negligible quantities of oxygen defects, as probed by the b / a lattice parameters ratios and solid‐state NMR. Operando X‐ray diffraction recorded during charge at C /2 reveals subtle differences between the samples (of different particle size, morphology, and carbon‐coating nature) in the crystallinity of the intermediate compositions formed within the Na3 V2 (PO4 )2 F3 –NaV2 (PO4 )2 F3 phase diagram. A new temperature‐controlled operando cell is used to determine this phase diagram at 0 °C, mostly unchanged compared to that of recorded at 25 °C. Very high charging and discharging rates are demonstrated and intermediate compositions can be spotted operando even up to 25 C rate at which the compositional phase diagram is only slightly altered compared to that recorded under equilibrium conditions. Optimized carbon‐coated Na3 V2 (PO4 )2 F3 shows exceptional rate and electrochemical cycling capabilities, as demonstrated by hard carbon//Na3 V2 (PO4 )2 F3 18650 prototypes of 75 Wh kg −1 that can be charged or discharged 4000 times at 1 C rate. Abstract : 18650 prototypes of 75 Wh kg −1 Na3 V2 (PO4 )2 F3 versus hard carbon demonstrate exceptional rate and electrochemical cycling capabilities with 4000 charge and discharge cycles performed at 1 C rate. An optimized carbon‐coated Na3 V2 (PO4 )2 F3 is shown to deliver promising electrochemical performance, at room temperature and at 0 °C, at very high rates, with no major modification of the phase diagram observed within the composition range Na3−1 V2 (PO4 )2 F3 .